Functional Connectivity of the Subcallosal Cingulate Cortex Identifies Differential Outcomes to Treatment with Cognitive Behavior Therapy or Antidepressant Medication for Major Depressive Disorder - Dunlop, Boadie W. (Am J Psychiatry, 2017)
OBJECTIVE: To inform the first-line treatment choice between cognitive behavior therapy (CBT) or an antidepressant medication for treatment-naïve adults with major depressive disorder by defining a neuroimaging biomarker that differentially identifies the outcomes of remission and treatment failure to these interventions. METHOD: Functional magnetic resonance imaging resting state functional connectivity analyses using a bilateral subcallosal cingulate cortex (SCC) seed was applied to 122 patients from the Prediction of Remission to Individual and Combined Treatments (PReDICT) study who completed 12 weeks of randomized treatment with CBT or antidepressant medication. Of the 122, 58 achieved remission (Hamilton Depression Rating Scale, HDRS) ≤7 at weeks 10 and 12); 24 were treatment failures (HDRS <30% decrease from baseline). A 2×2 ANOVA using voxel-wise subsampling permutation tests compared the interaction of treatment and outcome. ROC curves constructed using brain connectivity measures were used to determine possible classification rates for differential treatment outcomes. RESULTS: The resting state functional connectivity of three regions with the SCC was differentially associated with outcomes of remission and treatment failure to CBT and antidepressant medication, and survived application of the subsample permutation tests: left anterior ventrolateral/insula prefrontal cortex, dorsal midbrain, and left ventromedial prefrontal cortex. Using the summed SCC functional connectivity scores for these three regions, we demonstrated overall classification rates of 72–78% for remission and 75–89% for treatment failure. Positive summed functional connectivity was associated with remission with CBT and treatment failure with medication, whereas negative summed functional connectivity scores were associated with remission to medication and treatment failure with CBT. CONCLUSIONS: Imaging-based depression subtypes defined using resting state functional connectivity differentially identified an individual’s probability of remission or treatment failure with first-line treatment options for major depression. This biomarker should be explored in future research through prospective testing and as a component of multivariate treatment prediction models.